Характер психомоторних реакцій в осіб із різним рівнем фізичної працездатності - Волошин, Олена; Чень, Ірина; Волошин, Володимир; Voloshyn, Olena; Chen’, Iryna; Volodymur, Voloshyn (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Досліджували зорово-моторну реакцію, оцінку часових інтервалів і коректурну пробу задля вивчення специфіки психофізіологічних реакцій організму осіб з різним рівнем фізичної працездатності. За винятком швидкості зорово-моторної реакції, всі досліджувані показники мають якісно вищий рівень в осіб із середнім і високим рівнями індексу Руф’є та нормальною частотою серцевих скорочень. Experimental studies examined the visual-motor response and assessment of time intervals and proofreading test for the study of specific of psychophysiological responses of individuals with different levels of physical performance. It was measured the heart rate (HR), blood pressure and determined the index of Rufye’s test for the distribution of contingent of surveyed into groups according to their level of physical performance and general condition of their cardiovascular system. It was revealed that individuals with moderate and high scores of Rufye’s index characterized by the highest degree of reality of assessment of time intervals. Persons with increased heart rate have the lowest value of the level of concentration, tempo of execution and indicator of switching of attention. They are characterized by the value of time spending at proofreading test. All studied parameters (except for the speed of visual-motor response) have qualitatively higher level in individuals with medium and high levels of Ruf’ye index and normal heart rate.
The Character of Psycho-motor Reactions in Individuals with Different Levels of Physical Performance.
Keywords: психофізіологічний стан; рівень фізичної працездатності; зорово-моторна реакція; коректурна проба; оцінка часових інтервалів; psychophysiological state; proofreading test; visual-motor reaction; estimation of time intervals; level of physical performance